Association between stress hyperglycemic ratio and all-cause mortality in critically ill patients following cardiac surgery - Yuanli Yang; Ronglin Chen; Jian Xu; Sanming Yu; Linhai Sun; Ying Zhao (Medicine, 2026)
The stress hyperglycemic ratio (SHR) can be used as a reliable predictor of various adverse cardiovascular outcomes. However, there are fewer studies on the relationship between SHR and the risk of all-cause mortality in critically ill patients undergoing cardiac surgery (CS). Therefore, the aim of this study was to investigate the relationship between SHR levels and all-cause mortality in critically ill patients with CS admitted to the intensive care unit. Data from 3117 CS intensive care unit patients (Medical Information Mart for Intensive Care-IV) were analyzed. SHR values were categorized into 4 groups using equal-frequency binning to ensure uniform distribution across intervals. The primary outcomes were 30- and 180-day all-cause mortality, with secondary outcomes including 90- and 365-day all-cause mortality. Kaplan–Meier survival curves were employed to compare survival outcomes across SHR groups for both primary and secondary endpoints. To further evaluate the associations between SHR and mortality outcomes, Cox proportional hazards regression models were fitted, supplemented by restricted cubic splines analysis to investigate potential nonlinear relationships between SHR and the risk of death. Among 3117 participants, higher levels of the SHR index were significantly associated with increased all-cause mortality risk at 30, 90, 180, and 365 days (log-rank P < .001 by Kaplan–Meier analysis). Cox proportional hazards regression confirmed significantly elevated mortality risk in the highest SHR quartile at all timepoints. restricted cubic splines analysis revealed a J-shaped association between SHR and mortality, with inflection points at 0.94 (30-day) and 0.96 (365--day). Compared to patients with SHR levels below the inflection point, those with higher SHR levels had a 4.490-fold higher risk of 30-day all-cause mortality (hazard ratio: 4.490, 95% confidence interval: 2.944–6.848) and 3.701-fold higher risk of 365-day all-cause mortality (hazard ratio: 3.701, 95% confidence interval: 2.526–5.425). In critically ill patients following CS, higher SHR was significantly associated with increased all-cause mortality risk at 30, 90, 180 and 365 days postoperatively. SHR may serve as a prognostic marker to guide intensive care unit therapeutic strategies.